Centralized dynamics multi‐frequency GNSS carrier synchronization. Issue 3 (21st May 2019) - Bolla, Padma; Vilà‐Valls, Jordi; Closas, Pau; Lohan, Elena Simona
Abstract: In this article, we propose a new centralized multi‐frequency carrier tracking architecture using an adaptive Kalman filter to enhance the loop sensitivity and reliability of individual signal tracking in challenging signal environments. The main task of the centralized dynamics‐tracking filter is to effectively blend multiple frequency carrier phase observations in order to estimate the common geometric Doppler frequency of multiple‐frequency received signals. Conventionally, multi‐frequency signals are tracked independently with a fixed‐loop noise bandwidth tracking approach, which is suboptimal in time‐varying signal environments. A suitable collaboration in multiple‐frequency signal tracking using a centralized dynamics‐tracking loop enables robust carrier tracking even if some of the frequency channels are affected by ionospheric scintillation, carrier‐phase multipath, or interference. Additionally, computational efficiency of the multiple‐frequency tracking improves by using the proposed tracking loop architecture. Performance of the proposed multi‐frequency tracking‐loop architecture is verified with experiments using live multi‐frequency satellite signals collected from GPS Block‐IIF satellites under the influence of frequency‐selective interference signals.